Modified Anchor Shaped Post Core Design for Primary Anterior Teeth - R. Rajesh; Kusai Baroudi; K. Bala Kasi Reddy; B. H. Praveen; V. Sumanth Kumar; S. Amit (Case Reports in Dentistry)
Restoring severely damaged primary anterior teeth is challenging to pedodontist. Many materials are tried as a post core but each one of them has its own drawbacks. This a case report describing a technique to restore severely damaged primary anterior teeth with a modified anchor shaped post. This technique is not only simple and inexpensive but also produces better retention.